2019
DOI: 10.1186/s13021-019-0129-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the contribution of harvested wood products under greenhouse gas estimation: accounting under the Paris Agreement and the potential for double-counting among the choice of approaches

Abstract: Background: There are multiple approaches for estimating emissions and removals arising from harvested wood products (HWP) based on differences between when and where a given carbon stock change is calculated. At this moment, countries are free to use any HWP approach to prepare their annual greenhouse gas (GHG) inventory and determine emission reduction targets for their Nationally Determined Contributions (NDCs), although under the Paris Agreement (PA), the production approach is used for standard reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
0
19
0
1
Order By: Relevance
“…Norton et al, 2019; Searchinger et al, 2009). Decisions on the approach to reporting and accounting for bioenergy and other wood products were informed by consideration of impacts on incentives for forest harvest and trade in wood products, practicality of calculation and data availability (Cowie et al, 2006; Höhne et al, 2007; Houghton et al, 1997 Vol 3; Lim et al, 1999; Penman et al, 2003; Sato & Nojiri, 2019; Schlamadinger et al, 2007). As explained by Rüter et al (2019), emissions associated with wood products including bioenergy may be reported by the producing or consuming country, and may be based on carbon stock change in the forest or in the wood products pool, depending on the approach chosen by each party for reporting of harvested wood products (HWP).…”
Section: Reporting and Accounting For Bioenergymentioning
confidence: 99%
See 2 more Smart Citations
“…Norton et al, 2019; Searchinger et al, 2009). Decisions on the approach to reporting and accounting for bioenergy and other wood products were informed by consideration of impacts on incentives for forest harvest and trade in wood products, practicality of calculation and data availability (Cowie et al, 2006; Höhne et al, 2007; Houghton et al, 1997 Vol 3; Lim et al, 1999; Penman et al, 2003; Sato & Nojiri, 2019; Schlamadinger et al, 2007). As explained by Rüter et al (2019), emissions associated with wood products including bioenergy may be reported by the producing or consuming country, and may be based on carbon stock change in the forest or in the wood products pool, depending on the approach chosen by each party for reporting of harvested wood products (HWP).…”
Section: Reporting and Accounting For Bioenergymentioning
confidence: 99%
“…The issue of incomplete coverage for accounting could potentially have been overcome under the Paris Agreement, as all parties now have targets (their nationally determined contributions, NDCs) against which they are required to account. However, the disparity in sectors and emission sources covered in countries' NDCs, and inconsistency in the HWP accounting approach applied, perpetuates risks of double‐counting or omissions (Rüter et al, 2019; Sato & Nojiri, 2019). Within a country, the forest accounting approach used in the second commitment period of the Kyoto Protocol (2013–2020) allowed a policy‐driven increase in harvest, such as resulting from an increase in bioenergy, to be included in a country's ‘forest management reference level’, and therefore not counted as a debit in the land sector (Grassi et al, 2018).…”
Section: Reporting and Accounting For Bioenergymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, it remains unclear how the forest sector could be credited for this contribution to climate change mitigation. The Kyoto Protocol allowed accounting for changes in forest carbon stocks as a sink (UNFCCC‐COP3, ) and this was extended in the Durban conference of the parties (UNFCCC‐COP17, ) as well as the Paris Agreement to an additional accounting for carbon in wood products of wood industries (Sato & Nojiri, ; UNFCCC‐COP21, ). Following the definitions of the IPCC Guidelines for carbon sinks and products, the accounting of bioenergy remained a separate issue.…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture, forestry, and other land use (AFOLU) sectors are often the primary focus. For example, manure from American dairy farms [3], forest degradation in developing countries [4], broiler husbandry in Portugal [5], coastal wetlands in the United States [6], Canadian managed forest [7], harvested wood products in several countries [8], and drained organic soils in Germany [9] have been recently studied. Analysis in this first subdivision often focuses on developed countries.…”
Section: Introductionmentioning
confidence: 99%